PENGARUH PENGHINDARAN PAJAK DAN RISIKO PAJAK TERHADAP BIAYA UTANG (Studi Empiris Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2018) - Anggun Putri Setya Dewi; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the effect of tax avoidance and tax risk on debt costs, and tax risk as a moderating variable. The dependent variable in this study is the cost of debt. The independent variable in this study is tax avoidance, measured by the Cash Effective Tax Rate (ETR) proxy, and tax risk is measured by the standard deviation of tax avoidance. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2018. The number of samples used were 135 companies using purposive sampling. In this study there are five control variables (leverage, growth opportunities, ownership structure, volatility of income before tax and cash holding). The data processing program uses SPSS (Statistical Product and Service Solution). Version 23. The analytical method used in this study is the multiple linear regression test, the determinant coefficient test (R2), and the test of the significance of individual parameters (t-test). The results showed that the variable of tax avoidance doesn’t had a significant influence on the cost of debt, Tax risk had a significant influence on the cost of debt and Tax risk cannot moderate the effect of tax avoidance on debt costs.